ANALISIS FAKTOR YANG MEMENGARUHI PRESTASI BELAJAR MAHASISWI PRODI D-III KEBIDANAN STIKES MARANATHA KUPANG TAHUN 2020 - MARDIANA STEFANIA BHOKO; Matilda Bupu Ria; Maria Vilastry Nuhan (Unika Santu Paulus Ruteng, 2021)
Learning achievement is very important to summarize the results of the learning process that has been done so far. This study aims to analyze the factors that influence of learning achievement. Quantitative design study with cross sectional approach. 125 students of the Midwifery Study Program at STIKes Maranatha Kupang were selected as the randomly selected sample of the 278 female student population. The study was conducted in August 2020. Data was collected using questionnaires, attendance records, and student KHS (Study Result Cards). Data analysis used ordinal regression with the SPPS 22 application with a significance of p≤0.05. The results showed that the factors that affecting of student learning achievement were the student attendance rate in class (0.002), the role of the academic supervisor (p = 0.001), and student learning motivation (0.000). Achievement of good student learning achievement is not only determined by intrinsic factors such as motivation, but can also be influenced by extrinsic factors such as attendance levels and the role of supervisors.